Religious responses of ICU nurses to moral distress: A qualitative study - Foroozan Atashzadeh Shoorideh; Tahereh Ashktorab; Farideh Yaghmaei; Hamid Alavi Majd (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Nowadays, intensive care unit nurses face with numerous moral distress. Moral distress causes a series of responses in nurses. With recognizing these responses, strategies can be used for reducing them. This research was conducted to explain religious responses of ICU nurses to moral distress. Materials and Methods: This qualitative study (which is part of a doctoral thesis) with content analysis approach was done in order to describe of ICU nurses' religious responses to moral distress. In this study, the data were collected by semi-structured and deep interviews with 18 individual and two group interviews with clinical nurses whom working in different cities in Iran. A Purposive sampling and data analysis with conventional content analysis were done. Results: 26 nurses were participated in this study. During the process of content analysis, 5 subcategories, and 2 categories were obtained. These categories of ICU nurses 'religious responses to moral distress' included: "religious beliefs", and "Impairment of religious beliefs". Results of this study showed a firm faith in God and trust in him causes positive response. Weakness and insecurity in the faith cause negative response to moral distress. Main theme in this research was religious responses. Conclusion: Results of this study showed that ICU nurses use various positive and negative responses in deal of moral distress. Nurse administrators can help ICU nurses to diminish moral distress, learn the correct religious beliefs, and prevent harmful outcomes. Teaching religious beliefs, during college, empowering and enhancing the religious capacity is necessary for coping with moral distress. Keywords: religious response, nurses, moral distress, ICU, content analysis For downloading the full-text of this article please click here.